Efficacy and Safety of Intensive Blood Pressure Lowering on Cardiovascular Outcomes and Orthostatic Hypotension in Frail vs. Non-Frail Elderly Patients: A Systematic Review and Meta-Analysis - Dian Arfan As Bahri; Rose Dinda Martini; Roza Mulyana; Fandi Triansyah (HM Publisher, 2026)
Background: The management of hypertension in the older adult population presents a complex clinical challenge, particularly regarding the balance between cardiovascular risk reduction and the provocation of adverse events such as orthostatic hypotension. Frailty status complicates this dynamic, creating uncertainty regarding the optimal blood pressure target. Methods: A systematic review and meta-analysis investigated the efficacy and safety of intensive versus standard blood pressure lowering in frail compared to non-frail older adults. Databases were systematically searched for randomized controlled trials and their secondary analyses reporting cardiovascular outcomes and orthostatic hypotension stratified by frailty. Data were extracted and synthesized using a random-effects model, calculating pooled risk ratios and standardized mean differences to assess primary cardiovascular events and safety outcomes. Results: Ten primary studies met the inclusion criteria. Intensive blood pressure lowering significantly reduced the incidence of major cardiovascular events in both non-frail and frail cohorts. Surprisingly, intensive treatment did not increase the risk of orthostatic hypotension in frail patients and was associated with a protective effect against orthostatic hypotension in specific subsets. The risk of bias was generally low across the included trials. Conclusion: Intensive blood pressure control provides substantial cardiovascular benefits for older adults, irrespective of baseline frailty status. Furthermore, the aggressive lowering of blood pressure does not exacerbate the risk of orthostatic hypotension, challenging previous clinical hesitations. These findings support the cautious but deliberate implementation of intensive targets in the geriatric population, monitored closely by comprehensive geriatric assessments.